Study of the Feasibility of Regeneration of Central Worn-Out Textures of Ilam City Based on Urban Smart Growth Approach - pakzad azadkhani; mohammad Salavarzizadeh; Fatemeh Farogh Doost (تحقیقات کاربردی علوم جغرافیایی)
Deterioration of urban textures is an issue that most cities in Iran are faced with and the organization of such textures is of great importance. One of the safest and most practical solutions for urban planners is to assess the feasibility of regenerating such textures to determine the levels that can be regenerated and are relatively good and tolerable for urban society. Therefore, the present study aims to investigate the feasibility of regenerating worn-out textures of Ilam City based on urban smart growth approach using a descriptive-analytical methodology. The statistical population of the study includes residents of central worn-out texture of Ilam city (population: 12676 people), 384 of whom are selected as the sample of the study using cluster sampling method. The data collection tool is a researcher-made questionnaire that has been confirmed by face validity and Cronbach’s Alpha coefficient, turning out to be 0.701. Data analysis is done using single-sample t-test, fuzzy multi-criteria analytical hierarchy process (fuzzy AHP), and its integration with GIS layers. The findings show that the condition of worn-out textures of Ilam city is unsuitable in terms of urban smart growth approach. Evaluation of the digital strata shows that some indicators (including size of the sections, access to services, main and secondary access points) are in a good condition and others (including unused land, population density, gender ratios, active population, employment rate, and literacy rate) are in a poor condition. Finally, the results show that 2.3 hectares of the worn-out texture of Ilam City, including 22-Bahman Square, Ashrafi Esfahani St. where it crosses Resalat Intersection, the northern edge of Moghavemat Intersection, the northern edge of Imam Square, and the area around Koudak Park, have the highest priority for regeneration and revitalization.